Գրիգոր Սկևռացու աղոթքները - Մինասյան, Թամարա (Հայաստանի ազգային գրադարան)
Grigor Archimandrite Skevratsi, a follower of the famous clergyman and theologian Nerses of Lambron, was one of the outstanding public, political and cultural figures of medieval Armenia, who in his literary, cultural, religious, social and pedagogical activities was a worthy disciple of his teacher and carried on the traditions establishedby him. Grigor Skevratsi is a multi-genre author. He wrote in practically every genre of spiritual literature and left a legacy of odes and Church Hymns (sharakan), orations and sermons, exhortations and prayers, interpretations and translations. The current paper presents the prayers of Grigor Skevatsi. His theory of prayer is directly derived from the teaching of the school of Narek Monastery which is evidence of a continuity of tradition. Grigor Skevratsi expressed his views on prayer as the highest moment of spiritual life in a number of works, in the theologicalpoem “Instruction on the true Faith and the Virtuous and Pure Life” (“Khrat” (exhortation) «Բան խրատու վասն ուղիղ հաւատոյ և մաքուր վարուց առաքի- նութեան» («Խրատ»)), sermons, several small and large prayers. Skevratsi's prayers testify to his deep faith and high spiritual level.
Keywords: Ժառանգության պահպանություն